Association between GRIN2A promoter polymorphism and recovery from concussion. (6th December 2015) - McDevitt, Jane; Tierney, Ryan Timothy; Phillips, Jacqueline; Gaughan, John P.; Torg, Joseph S.; Krynetskiy, Evgeny
Abstract: Objective : To determine genetic variability within the N-methyl-D-aspartate receptor 2A sub-unit ( GRIN2A ) gene promoter and its association with concussion recovery time. The hypothesis tested was that there would be a difference in allele and/or genotype distribution between two groups of athletes with normal and prolonged recovery. Methods : DNA was extracted from saliva collected from a total of 87 athletes with a physician-diagnosed concussion. The (GT) variable number tandem repeats (VNTR) within the promoter region of GRIN2A was genotyped. The long (L) allele was an allele with ≥25 repeats and the short (S) allele was an allele with <25 repeats in the GT tract. Participants' recovery time was followed prospectively and was categorized as normal (≤60 days) or prolonged (>60 days). Results : LL carriers were 6-times more likely to recover longer than 60 days following the concussive event ( p  = 0.0433) when compared to SS carriers. Additionally, L allele carriers were found more frequently in the prolonged recovery group ( p  = 0.048). Conclusion : Determining genetic influence on concussion recovery will aid in future development of genetic counselling. The clinical relevance of genotyping athletes could improve management of athletes who experience concussion injuries.